Morphological Stylistic Analysis found in Langston Hughes’s Poem “Harlem” - Zahara, Ayuna; Hidayat, Chatrine Aulia; Rangkuti, Rahmadsyah (Universitas Muhammadiyah Mataram, 2023)
This study conducts a morphological stylistic analysis of Langston Hughes's renowned poem